Do In Shiatsu Massage dan Latihan Keseimbangan dalam Menurunkan Risiko Jatuh pada Lansia - Bettywati E. Tumanggor; Yellyanda Yellyanda; Debbie Nomiko; Mohd. Syukri (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of shiatsu massage and balance exercises in reducing the risk of falling in older people. This quasi-experimental study used a Pretest-Posttest Control Group design. The results showed that the condition of the do in the shiatsu massage group before the intervention had a high risk of 8 (47.05%), then decreased to 2 (29.41%) after the intervention. The pre-test conditions in the balancing exercise group showed a high risk of 5 (29.41%) and decreased to 1 (5.88%) after the intervention. This indicates that both interventions reduce the risk of falling in older people. Statistically, using the Paired t-test showed that the two interventions significantly reduced the risk of losing in the elderly p-value <0.05. In conclusion, the intervention of do in shiatsu massage and balance training reduces the risk of falling in older people. Keywords: Do In Shiatsu Massage, Elderly, Balance Exercise, Fall Risk